Analyzing the Needs of Pre-service Teacher Education Students for Flipbook Learning Resources: Enhancing Understanding and Engagement with Educational Materials - Siti Dewi Maharani; Laihat Laihat; Budiansyah Budiansyah; Rahmi Susanti; Siti Swasti Eka Dewie; Sabrina Ramadhani; Anik Sundari (STAI Hubbulwathan Duri, 2024)
In today's rapidly advancing landscape of information and communication technology, the adoption of technology-based learning tools such as Flipbooks is increasingly essential for optimizing educational experiences. Commonly known as flipping books, Flipbooks offer a dynamic way to engage with learning materials. This study investigates the specific needs of pre-service elementary school teacher education students (batch 2) from the Faculty of Literature and Education at Sriwijaya University regarding the use of Flipbook learning resources. The focus is on how these resources can enhance students' understanding of course content and improve interaction with educational materials. Employing qualitative research methods, including interviews and questionnaires, the study involved 36 participants. Findings indicate a substantial demand, with 94% of the respondents expressing a need for Flipbook-based teaching modules that cater to courses on student understanding and learning materials. These results underscore the potential benefits of integrating digital learning resources in teacher education, aiming to meet student needs effectively and enhance educational outcomes.